2022
DOI: 10.1111/1475-6765.12513
|View full text |Cite
|
Sign up to set email alerts
|

Emotions, governmental trust and support for the restriction of civil liberties during the covid‐19 pandemic

Abstract: The Covid-19 pandemic brought unprecedented governmental restrictions to personal and political freedoms. This article investigates individual-level differences in mass support for the restriction of civil liberties during the first wave of the Covid-19 pandemic. Employing theories of affect and decision making, it assesses the extent to which different emotional reactions toward the pandemic influenced attitudes toward mobile phone surveillance and the implementation of curfews. We test our hypotheses in five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 90 publications
(153 reference statements)
3
14
0
Order By: Relevance
“…The most recent scholarship on these three questions increasingly probes their empirical interdependencies. For example, drawing connections between restrictions on liberties and public trust, Vasilopoulos et al ( 2022 ) suggest that the ‘Covid‐19 pandemic provides an ideal testbed for understanding the public’s commitment to individual liberties’ (p. 2). Employing data from Austria, France, Germany, Italy and the UK, they find that ‘experiencing fear about COVID‐19 had a strong positive impact’ on supporting restrictions on civil liberties (p. 2); ‘the findings indicate that emotions moderate the impact of trust toward the government, a key variable for supporting the restriction of civil liberties (…) experiencing fear was associated with higher acceptance of civil liberty restrictions’ (p. 2).…”
Section: Democratic Dynamicsmentioning
confidence: 99%
“…The most recent scholarship on these three questions increasingly probes their empirical interdependencies. For example, drawing connections between restrictions on liberties and public trust, Vasilopoulos et al ( 2022 ) suggest that the ‘Covid‐19 pandemic provides an ideal testbed for understanding the public’s commitment to individual liberties’ (p. 2). Employing data from Austria, France, Germany, Italy and the UK, they find that ‘experiencing fear about COVID‐19 had a strong positive impact’ on supporting restrictions on civil liberties (p. 2); ‘the findings indicate that emotions moderate the impact of trust toward the government, a key variable for supporting the restriction of civil liberties (…) experiencing fear was associated with higher acceptance of civil liberty restrictions’ (p. 2).…”
Section: Democratic Dynamicsmentioning
confidence: 99%
“…During pandemics, research has repeatedly shown that feelings of fear and threat increase the likelihood of complying with public health advice, also during the most recent COVID‐19 crisis (Harper et al, 2021 ; Jørgensen et al, 2021 ). Vasilopoulos and coauthors ( 2022 ) found that in five European countries fear increases support for restrictive measures during the COVID‐19 pandemic, even if these measures restrict civil liberties. Other negative emotions, for instance anger, had no significant impact.…”
Section: Emotional Rhetoric In Political Communicationmentioning
confidence: 99%
“…In doing so, research has shown that they make extensive usage of negative emotions such as fear (Widmann, 2021 ). Yet, during the COVID‐19 crisis, increased levels of fear might benefit their political competitors, as it can increase trust in governments (Schraff, 2020 ; Vasilopoulos et al, 2022 ) and compliance with governmental advice (Jørgensen et al, 2021 ; Vasilopoulos et al, 2022 ).…”
Section: Emotional Rhetoric In Political Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides emotions, people’s perceived efficacy of control and prevention measures, their adherence to control measures, and their attitude toward the government (such as satisfaction with the government, trust in the government, and perceptions of the responses of the government) are important factors associated with confidence in fighting the pandemic [ 1 , 5 , 20 , 21 , 22 ]. Previous studies investigating confidence to combat the pandemic suggested that the perceived efficacy of control measures, such as COVID-19 vaccination, and quarantine will affect the execution of these measures, accordingly affecting residents’ beliefs in controlling the pandemic [ 6 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%